2018
DOI: 10.1016/j.molcel.2018.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Effector ppGpp Potentiates the Inhibition of Transcript Initiation by DksA

Abstract: DksA and ppGpp are the central players in the stringent response and mediate a complete reprogramming of the transcriptome. A major component of the response is a reduction in ribosome synthesis, which is accomplished by the synergistic action of DksA and ppGpp bound to RNA polymerase (RNAP) inhibiting transcription of rRNAs. Here, we report the X-ray crystal structures of Escherichia coli RNAP in complex with DksA alone and with ppGpp. The structures show that DksA accesses the template strand at the active s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
114
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 60 publications
(132 reference statements)
5
114
1
Order By: Relevance
“…Movies S1-S6 Supplemental References (26-42) E. coli RNAP core enzyme E. coli RNAP core enzyme was prepared from E. coli strain BL21 Star (DE3) (ThermoFisher) transformed with plasmid pVS10 (26; encodes E. coli RNAP β' with C-terminal hexahistidine tag, β, α, and ω subunits), as described (27). The product (purity >95%) was stored in aliquots in RNAP storage buffer (10 mM Tris-HCl, pH 7.6, 100 mM NaCl, 0.1 mM EDTA, and 5 mM dithiothreitol) at -80ºC.…”
Section: Methodsmentioning
confidence: 99%
“…Movies S1-S6 Supplemental References (26-42) E. coli RNAP core enzyme E. coli RNAP core enzyme was prepared from E. coli strain BL21 Star (DE3) (ThermoFisher) transformed with plasmid pVS10 (26; encodes E. coli RNAP β' with C-terminal hexahistidine tag, β, α, and ω subunits), as described (27). The product (purity >95%) was stored in aliquots in RNAP storage buffer (10 mM Tris-HCl, pH 7.6, 100 mM NaCl, 0.1 mM EDTA, and 5 mM dithiothreitol) at -80ºC.…”
Section: Methodsmentioning
confidence: 99%
“…During the stringent response, ppGpp is produced in high quantities, binds to RNAP, destabilizes RP O at ribosomal RNA (rrn) and other promoters, and inhibits isomerization of RP C to RP O at rrn and other promoters (38). ppGpp binds to two distinct sites in RNAP, "site 1" located at the interface between RNAP β' and ω subunits, and "site 2" located near the RNAP secondary-channel β' rim helices (37,(39)(40)(41). It is thought that ppGpp exerts its effects on RNAP through an allosteric mechanism, but details are unclear (37,(40)(41)(42).…”
Section: Effects Of Small-molecule Inhibitors and Effectors On Clamp mentioning
confidence: 99%
“…The near-atomic resolution X-ray crystal structure of E. coli RNAP was determined first as holoenzyme containing σ 70 (Murakami, 2013). X-ray crystal and cryo-electron microscopy (cryo-EM) structures of E. coli RNAP are now available in several forms such as holoenzymes containing alternative σ factors (Liu et al, 2016; Yang et al, 2015), promoter DNA complexes (Glyde et al, 2017; Zuo and Steitz, 2015), elongation complex (Kang et al, 2017), in complex with transcription factors (Bae et al, 2013; Liu et al, 2017; Molodtsov et al, 2018), and with inhibitors/antibiotics (Bae et al, 2015; Chen et al, 2017; Degen et al, 2014; Molodtsov et al, 2015; Molodtsov et al, 2013), providing details of the structure and function of E. coli RNAP transcription and regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies identified another ppGpp binding site near the secondary channel of RNAP, which is ~60 Å away from the site 1. The second ppGpp binding site is formed only in the presence of the RNAP binding transcription regulator DksA (Molodtsov et al, 2018; Ross et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation